(3EJaGb GdJMcje hGdeTcdGJ GdYedjI hGdbGfhfjI aj GdYdGbGJ GdNGUI GdOhdjIs - (3CTQa YHO GdYdje(B, (3GdQaGYjs ((3GdEScfOQjI(B:s (3OGQ GdacQ GdYQHj(B,s, 2002)
(3eaghe GdfXGe GdYGe GdOGNdj(B- (3eaghe GdJMcje(B- (3eTGcd GdfXGe GdYGe aj GdYdGbGJ GdYGeI(B- (3eTGcd GdfXGe GdYGe aj YdGbJg HGJaGb GdJMcjes
Keywords: (3GdJMcjes; (3GdYdGbGJ GdYGeIs